Drug Tolerant Anti-drug Antibody Assay for Infliximab Treatment in Clinical Practice Identifies Positive Cases Earlier - Kharlamova, Nastya; Hermanrud, Christina; Dunn, Nicky; Ryner, Malin; Hambardzumyan, Karen; Vivar Pomiano, Nancy; Marits, Per; Gjertsson, Inger; Saevarsdottir, Saedis; Pullerits, Rille; Fogdell-Hahn, Anna (Frontiers in Immunology, 2020)
A subgroup of patients treated with infliximab do not respond to the treatment and one of the causes of this are anti-drug antibodies (ADA). Measuring drug level and ADA could lead to a more personalized and efficient treatment, if used optimally, and enable identification of ADA-positive patients, before the underlying disease flares or allergic reactions occur. With a drug-tolerant ADA assay, measuring ADA irrespective of drug levels in the sample, we determined the impact of ADA on treatment failure to infliximab. The aims of this study were to estimate the real-life optimal serum infliximab (sIFX) level and set a clinical threshold value of a drug-tolerant ADA assay. Trough levels of sIFX were measured with ELISA. Free ADA was measured with two drug-sensitive methods (ELISA and a bioassay) and one drug-tolerant method (PandA). Two real-life cohorts treated with infliximab were included; a cross-sectional cohort including patients with inflammatory rheumatic diseases (n=270) and a prospective cohort of rheumatoid arthritis (RA) patients (n=73) followed for one year. Normal range of sIFX was estimated from the prospective study and an arbitrary optimal drug level was set to be between 1 µg/mL and 6 µg/mL Using this range, optimal sIFX was found in only 60% (163/270) of the patients in the cross-sectional cohort. These patients had significantly better treatment response than those with a drug level under 1 µg/mL, who had an ADA frequency of 34% (19/56) using the drug-tolerant method. In the prospective cohort, the drug-tolerant assay could identify 34% (53/155 samples) as ADA positive in samples with sIFX level more than 0.2 µg/mL. ADA were seldom detected in patients with more than 1µg/mL sIFX, with three interesting exceptions. A clinically relevant ADA threshold was determined to be more than 3 RECL as measured with the drug-tolerant assay. In real-life setting, there was a substantial number of patients with suboptimal drug levels and a proportion of these had ADA. Both too low and too high drug levels correlated with worse disease, but for different reasons. Adding a drug-tolerant assay enabled detection of ADA earlier and regardless of drug level and time of sampling.